2023
DOI: 10.3390/ijms241915029
|View full text |Cite
|
Sign up to set email alerts
|

The MADF-BESS Protein CP60 Is Recruited to Insulators via CP190 and Has Redundant Functions in Drosophila

Larisa Melnikova,
Varvara Molodina,
Valentin Babosha
et al.

Abstract: Drosophila CP190 and CP60 are transcription factors that are associated with centrosomes during mitosis. CP190 is an essential transcription factor and preferentially binds to housekeeping gene promoters and insulators through interactions with architectural proteins, including Su(Hw) and dCTCF. CP60 belongs to a family of transcription factors that contain the N-terminal MADF domain and the C-terminal BESS domain, which is characterized by the ability to homodimerize. In this study, we show that the conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The insulators discovered in Drosophila [75][76][77] are able to activate target genes ([77-79], (review, [80])). The insulator proteins form associations that bind DNA in varying sites depending on composition of the association of proteins, and CHRIZ/CHROMATOR is a member of this association [81][82][83][84].…”
Section: The Organization Of Two Gene Types In the Drosophila Genomementioning
confidence: 99%
“…The insulators discovered in Drosophila [75][76][77] are able to activate target genes ([77-79], (review, [80])). The insulator proteins form associations that bind DNA in varying sites depending on composition of the association of proteins, and CHRIZ/CHROMATOR is a member of this association [81][82][83][84].…”
Section: The Organization Of Two Gene Types In the Drosophila Genomementioning
confidence: 99%
“…The CP190 and Mod(mdg4)-67.2 proteins are simultaneously required for the activity of the Su(Hw)-dependent complex and its recruitment to chromatin [44]. Su(Hw)-dependent complexes may also include other proteins, such as HIPP1 [47][48][49][50], CP60 [51,52], and RNA-binding proteins [53][54][55]. Several studies have suggested the participation of the CP190 and Mod(mdg4)-67.2 proteins in maintaining long-distance interactions [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%